URDU-THE STRATEGY FOR WORLD-PEACE BEFORE THE PROPHETHOOD OF MUHAMMAD PBUH - A HISTO-GEOGRAPHICAL STUDY - zahid Latif; Zain ul Abdin (دی اسکالر)
Before the arrival of Muhammad Arabi, the condition of the land of Arab was such that the humanity was groping in the dark, the human conscience has become filthy with ignorant ideas and norms of the society had been deteriorated to its lowest. The roots of humanity had become hallow due to the excessive indulgence of man in luxury and at the same time it was a condition of high deprivation in terms of knowledge. In addition to it, ignorance and barbarism were in prevalence, the religions were thoroughly circumscribed, the divine religions had been tempered with and lost their authenticity and reverence and become soulless and motionless hallow structure with some superstitious and mundane customs left in them. Prior to the advent of Islam whether it was the Roman Empire or the Sassanid Empire of Persian or Jewish culture and civilization or Indian eroticism and untouchability or Bedouin or jingoistic features of Arab land or Monarchy of China, every system and civilization was littered with barbarism and bloodshed of humanity and no one was expected to talk about humanity or the protection of rights of humanity. There was no hope at all that any savior of humanity may emerge on the horizon who may promote the lesson of rights and justice, peace and reconciliation, or the one who may uphold the cause of peace, justice, wisdom and reconciliation. The world was devoid    of such lexicon as peace, justice, and equality. Prior to the Holy Prophet of Allah, Muhammad (PBUH), there were some voices of reason that were raised as they were tired of the barbarism and bloodshed; these voices are called unwarranted pledge (Half ul Fuzool). But this ray of hope had the capacity to illuminate it might have illuminated only the Arab land with its light and only the last Prophet of Allah might have verified it.